2017
DOI: 10.1186/s12885-017-3347-9
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in working-age cancer survivors: a register-based study

Abstract: BackgroundAnxiety and depression can be a long-term strain in cancer survivors. Little is known about the emotional situation of cancer survivors who have to deal with work- and family-related issues. The purpose of this study was to investigate anxiety and depression in working-age cancer survivors and associated factors.MethodsA register-based sample of 3370 cancer survivors (25 to 55 years at time of diagnosis) diagnosed up to six years prior to the survey was recruited from two German cancer registries. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 41 publications
7
70
0
6
Order By: Relevance
“…Depression and anxiety also contribute to long‐term strain in cancer patients. In a recent survey of 3,370 survivors, 40% reported moderate to high anxiety, and in approximately 20%, moderate to high levels of depression lasted up to 6 years post‐diagnosis (Inhestern et al, ). Depression can lead to serious consequences that include worsening quality of life (Higginson & Costantini, ), lower adherence to anticancer treatments (Mathes, Pieper, Antoine, & Eikermann, ), suicide (Henriksson, Isometsa, Hietanen, Aro, & Lonnqvist, ), prolonged hospital stays (Prieto et al, ), and reduced survival (Pinquart & Duberstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety also contribute to long‐term strain in cancer patients. In a recent survey of 3,370 survivors, 40% reported moderate to high anxiety, and in approximately 20%, moderate to high levels of depression lasted up to 6 years post‐diagnosis (Inhestern et al, ). Depression can lead to serious consequences that include worsening quality of life (Higginson & Costantini, ), lower adherence to anticancer treatments (Mathes, Pieper, Antoine, & Eikermann, ), suicide (Henriksson, Isometsa, Hietanen, Aro, & Lonnqvist, ), prolonged hospital stays (Prieto et al, ), and reduced survival (Pinquart & Duberstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a report that as age increased, anxiety decreased signi cantly; however, age was not a signi cant predictor of depression [24]. A study on anxiety and depression in working-age cancer survivors reported that higher anxiety was associated with younger age; nonetheless, no signi cant association between depression and age was found [25]. In our study there was no signi cant difference between anxiety and age; nevertheless, signi cant increases in depression and psychological distress were reported as age increased in the univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Enfatiza-se variável significante quanto à presença de sintomas de depressão, devido às diferentes abordagens (pacientes diagnosticados (6,14) ou não clinicamente (4,(8)(9)15) ) e instrumentos utilizados, como IDB (3,5,8,(16)(17) , Center for Epidemiologic Studies Depression Scale ((7) , Escala de Depressão Geriátrica (9) , Escala Hospitalar de Ansiedade e Depressão (4,(14)(15)(16)(17)(18)(19) , Self-rating Depression Scale (20) .…”
Section: Discussionunclassified
“…Em estudo realizado com 3.370 sobreviventes de câncer na Alemanha, fatores como estar desempregado, receber pouco apoio social, estar sem tratamento, menor tempo desde o diagnóstico, saúde física prejudicada e pertencer à família de baixa renda obtiveram associações estatisticamente significantes para presença de maiores escores de depressão. Apuraram que mulheres ou homens com câncer de órgão genital ou câncer hematológico tiveram associações estatisticamente significantes a escores mais altos de depressão, em comparação com sobreviventes com câncer de mama (19) .…”
Section: Discussionunclassified